2017
DOI: 10.1002/hep4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Rate of seeding with biopsies and ablations of hepatocellular carcinoma: A retrospective cohort study

Abstract: Biopsies of liver masses that prove to be hepatocellular carcinomas (HCCs) are associated with a risk of seeding the abdominal or chest wall with tumor cells. The reported frequency of seeding varies greatly in the literature. We performed a retrospective cohort study in a large integrated health care system to examine rates of seeding in patients with HCC who had targeted liver biopsies, ablations, or both performed by community radiologists. We reviewed pathology and radiology records to determine the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
0
17
0
3
Order By: Relevance
“…89 Others consider sampling error or needle tract seeding of HCC cells as important limitations. 90 These issues are not relevant when collecting liquid biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…89 Others consider sampling error or needle tract seeding of HCC cells as important limitations. 90 These issues are not relevant when collecting liquid biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the 6 patients with seeding had biopsy with a coaxial system, but this patient underwent RFA in the same session. Abdominal wall metastasis occurred 33 months later [22]. Although the impact of biopsy and/or ablation on the risk of seeding is not clear yet, some authors recommend to avoid biopsy when ablation is intended.…”
Section: Discussionmentioning
confidence: 99%
“…The most quoted study about seeding risk is a meta-analysis that showed a rate of 2.7% in 1340 biopsies[69]. Nevertheless, adding three more recent series to this meta-analysis we would obtain much lower rates of seeding, even less than 1%[70-72]. Moreover, in most of the reported cases of seeding, its clinical impact is mitigated by the observation that it was usually treated successfully by resective or ablative treatments and did not cause relevant morbidity or mortality[72,73].…”
Section: Use Of Liver Biopsy In Clinical Management Of Hcc: Pros and mentioning
confidence: 99%